Sexual Function in Breast Cancer Patients: A Review of the Literature - Helena Castillo; Eduard Mension; Isaac Cebrecos; Sònia Anglès; Camil Castelo-Branco (IMR Press, 2022)
Background: Breast cancer (BC) is the most prevalent cancer among females worldwide. Despite having survival rates beyond 90% in 5 years nowadays, BC has also the highest rates of lost disability-adjusted life years (DALYs) among all cancers. Sexual dysfunction (SD) is one of the most important causes of the problem, affecting between 40-80% of BC survivors. However, SD remains underdiagnosed and undertreated in the clinical practice. Therefore, this review is aimed to evaluate the assessment of SD in Breast Cancer Survivors (BCS) as well as specific causes affecting their sexual function and the potential therapeutic options for these patients. Methods: In December 2021, a search of observational studies evaluating the sexual function in BCS was performed through Ovid Medline, Embase, PubMed, Cochrane register of controlled trials (CCTR), Cochrane database of systematic reviews (CDSR), Cumulative Index to Nursing & Allied Health Literature (CINAHL) and Google scholar to identify potentially relevant publications. Articles that evaluated non-gynecological cancers were excluded, as well as those focusing on the sexuality of men. Results: Despite being such a prevalent entity and given the particularities of how BC affects the sexuality of patients, SD is not usually discussed in the clinical practice in BCS for various reasons, remaining therefore underdiagnosed and undertreated. SD in BC patients has a multifactorial aetiology, including among others, the effect of BC treatments (related to vaginal mucosae, fatigue, and joint pain), the psychological impact of the diagnostic itself and sociocultural influences related to the alteration of the breast. Various strategies have been suggested to treat SD in BC patients, including pharmacological, physical and psychological options. Evidence shows that vaginal moisturizers and psyco-educational therapies focusing on sexual health and couple-based ones improve sexual function; while systemic treatments and general psychological therapy have not demonstrated benefit. Regarding exercise programmes, body image perception has shown to be improved after a one-year strength training program. Conclusions: SD is a multifactorial condition that affects the quality of life of millions of BCS worldwide, severely underdiagnosed and undertreated up to date. A systematic assessment of sexual function in BCS could be useful to diagnose all cases prematurely to give adequate care and prevent its worsening. Specific treatment options for BCS are key potential investigation targets for the near future.